Balancing Degradability and Physical Properties of Amorphous Poly(d, l‐lactide) by Making Blends. Issue 6 (24th September 2021) - Kumar, Anil; Weig, Alfons R.; Agarwal, Seema
Abstract: The problem in using the existing biodegradable polymers for day‐to‐day commodity and specialty applications (non‐physiological) is the trade‐off between the degradability and physical properties of polymers. Therefore, the authors study the properties of polyester films made by solution blending of amorphous poly(d, l ‐lactide) and semi‐crystalline poly(l, l ‐lactide) (PLLA) with an aim to achieve a good balance of mechanical properties and degradability under environmental conditions. The degradation test using proteinase K enzyme shows faster degradation of blends in comparison to homopolymers by weight loss. Faster fragmentation of blends and fragments of lower masses in comparison to PLLA is also seen in immature compost with bulk degradation as the main mechanism of degradation. A detailed investigation shows increased crystallinity and the formation of crystalline stereo‐complex in fragmented samples that may limit degradation after a stage causing microplastics persisting for a longer period. Therefore,  further degradation studies in compost for at least 8–10 weeks are recommended. Other environmental sinks, such as activated sludge water, fresh, and seawater, provide either extremely slow or no degradation excluding the use of such blends for applications intended for these sinks. In future, smart solutions are required to enhance the degradation of polylactide in different environmental sinks. Abstract : Detailed studies with the blends of amorphous and semi‐crystalline polylactide show reduced crystallinity and good mechanical properties of pristine samples with the faster enzymatic degradability and fragmentation in immature industrial compost. An increase in crystallinity and stereo‐complex formation during composting suggests changed degradation kinetics on prolonged degradation time. No degradation is observed in water bodies in one year.